المحدثون والرواة الكُرد الشيعة إلامامية خلال القرون 2-5ه/8-11م - ALI , KARWAN ABDULAZEEZ MAHAMMED; TOFIQ, ALI; ZRAR SADEEQ (Journal of Duhok University, 2023)
The jurisprudential sources of the Twelver Shiites dealt with the names of some Kurdish hadith scholars during the centuries 2-5 AH / 8-11 CE, where their names were mentioned with their explicit affiliation to their Kurdish nationality, as well as the affiliation of others to Kurdish cities such as al-Dinur, Sinjar and Karmisin, like the rest of the Shiite men and hadiths. Aspects, whether personal, scientific or even doctrinal religious, but most of them lived with the Twelver imams and assumed a good position with them, and they were among their close companions, and most of them lived in the city of Kufa, the center of the Imamiyyah, and they also transmitted many hadiths, narrations and religious texts that serve the idea of ​​Shiism from the imams duodenum. The presence of the Kurds among the Shiite modernists constituted a small percentage, compared to the rest of the nationalities present in the region, in addition to the huge amount enjoyed by the Shiite jurisprudence. The passage of time when the first beginnings of the codification of the Imami jurisprudence constituted the golden stage for the Kurdish hadiths before the spread of the ideas of the Shiite jurists, as the mention of the names of the hadiths and the Kurdish narrators gradually diminished, and ended with mentioning their tribes and the names of their cities instead of their nationality, such as the hadith Muhammad ibn Wahban al-Danbali .